LEARNING VOCABULARY USING FLASHCARDS FOR KIDS - ERNITA DAULAY (VISION, 2016)
The use of flashcards had affected the kids‘ activity in learning the words during the classroom activity. For examples, guessing and matching game in pairs were also effective to make the kids‘ motivation to learn getting better. Flashcards are so easy, so simple and so unassuming that learners often underestimate their power. In this case, the use of flashcards could help the kids to recognize the vocabulary of common nouns. Flashcards are quite effective because they promote the act of repetition. Because of their inherent simplicity, which we’ve already talked about, flashcards easily lend themselves to repetition. That’s why they’re so freakin’ awesome. They’re simple and unassuming, but they can pack a mean punch.Keywords: Teaching English For Kids, Vocabulary Teaching and Flashcards